Non-Fictional Interwar Narratives by English Writers - Barbara PUSCHMANN-NALENZ (E-REA)
The article presents a comparative reading of three nonfictional interwar narratives by British writers who are also well-known as authors of fiction or poetry. Siegfried Sassoon’s Memoirs of an Infantry Officer (1930) and Robert Graves’s Good Bye to All That (1929) present their authors’ experiences in war and peace times. Both had volunteered for the First World War and were deeply disillusioned about the meaninglessness of the sacrifice of lives. The borderlines between fiction and nonfiction often become blurred in these texts, despite their different conceptual approach. George Orwell’s Homage to Catalonia (1938) about the Spanish Civil War and the end of the 1930s connects his personal report about a war with his criticism of the conservative British establishment. His essay displays the writer’s engagement with politics and socialism added to his fascination with Spain. Aware of contemporaneous literary texts by the same writers my article aims at defining major counterdistinctive generic features of the different nonfictional narratives with their varying degree of fictionalisation.